2015
DOI: 10.1016/j.virol.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in pancreatic cancer cells by vesicular stomatitis virus

Abstract: Effective oncolytic virus (OV) therapy is dependent on the ability of replication-competent viruses to kill infected cancer cells. We previously showed that human pancreatic ductal adenocarcinoma (PDAC) cell lines are highly heterogeneous in their permissiveness to vesicular stomatitis virus (VSV), in part due to differences in type I interferon (IFN) signaling. Here, using ten human PDAC cell lines and three different VSV recombinants (expressing ΔM51 or wild type matrix protein), we examined cellular and vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 62 publications
(139 reference statements)
2
21
0
Order By: Relevance
“…Recently, we showed that VSV-DM51 was able to induce apoptosis efficiently in 7 out of 10 tested human PDAC cell lines, and determined that the VSV-mediated apoptosis activation mechanism depends on both the VSV M protein and the PDAC cell line [86]. Three cell lines constitutively expressing high levels of ISGs were resistant to apoptosis under most experimental conditions, even when VSV replication levels were dramatically increased by Jak inhibitor I treatment [86]. We discuss different approaches to increase direct oncotoxicity of VSV-based OV therapy in more detail in the following section.…”
Section: Other Approaches To Improve Vsv Oncoselectivitymentioning
confidence: 99%
“…Recently, we showed that VSV-DM51 was able to induce apoptosis efficiently in 7 out of 10 tested human PDAC cell lines, and determined that the VSV-mediated apoptosis activation mechanism depends on both the VSV M protein and the PDAC cell line [86]. Three cell lines constitutively expressing high levels of ISGs were resistant to apoptosis under most experimental conditions, even when VSV replication levels were dramatically increased by Jak inhibitor I treatment [86]. We discuss different approaches to increase direct oncotoxicity of VSV-based OV therapy in more detail in the following section.…”
Section: Other Approaches To Improve Vsv Oncoselectivitymentioning
confidence: 99%
“…The human PDAC cell line HPAF-II, which showed the highest level of resistance to VSV in our previous studies, was the main focus of this study (26)(27)(28)(29)(30). In addition, many experiments included Hs766T, another VSV-resistant human PDAC cell line, as well as two VSV-permissive human PDAC cell lines, MIA PaCa-2 and Suit2.…”
Section: Vsv Attachment To Hpaf-ii Cells Is Impairedmentioning
confidence: 99%
“…Particularly, VSV vectors have been subjected to aggressive pancreatic ductal adenocarcinoma (PDAC) showing superiority to Sendai virus and RSV in 13 clinically relevant human pancreatic cell lines, although the response varied from one cell line to another [85]. Moreover, evaluation in ten PDAC cell lines of three VSV vectors expressing the wild-type matrix protein or ∆M51 showed activation of VSV-mediated apoptosis [86]. However, high constitutive expression of IFN-stimulated genes (ISGs) was discovered in three cell lines, which also contributed to resistance to apoptosis.…”
Section: Self-replicating Rna Virus-based Vaccinesmentioning
confidence: 99%